2016
DOI: 10.7860/jcdr/2016/17856.7691
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Rationality of Fixed Dose Combinations Approved in CDSCO List

Abstract: Introduction: Fixed Dose Combination (FDC) is highly popular in the Indian pharmaceutical market and has been particularly flourishing in the last few years. Though rationality status is not clear, the pharmaceutical industry has been manufacturing and marketing FDCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 4 publications
3
18
0
Order By: Relevance
“…Several studies have reported that the huge amounts of FDC's have no rational basis. 2,5,7,15,16 In a study done by Krunal Dalal et all, nearly 52% of the FDC approved between 2009-2014 are irrational.…”
Section: Series1mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that the huge amounts of FDC's have no rational basis. 2,5,7,15,16 In a study done by Krunal Dalal et all, nearly 52% of the FDC approved between 2009-2014 are irrational.…”
Section: Series1mentioning
confidence: 99%
“…6 In a recent analysis, out of the 264 FDCs approved in India, only 54 FDCs were found to be rational and for the remaining FDCs, the safety and effectiveness remains a matter of investigation. 7 To be noted, although recently in March 2016, more than 324 Fixed Dose Combinations marketed in India are banned, still many of them are commonly prescribed and available as over the counter. 8 A study assessing knowledge of medical practitioners about rational fixed dose combination prescribing is needed because of the growing concern of irrational FDCs flooding the market.…”
Section: Introductionmentioning
confidence: 99%
“…Careful scrutiny of the Drugs and Cosmetics Act and subsequent amendments thereof, leads us to believe that there is no evident ambiguity in the licensing authorities of CDSCO and SLA, as the licensing powers have always been with CDSCO. This opinion is seconded in the academic reports [11,34,35].…”
Section: Discussionmentioning
confidence: 95%
“…The parameters in the toolkit state that the FDC should have a marketing status in different countries, clear ‘product information’ for the indicated diseases with information leaflets, a full high-quality data set, data for marketing authorization, well-characterized safety and efficacy including compliance with a suitable code of good manufacturing practice (GMP) during manufacture, etc. Such information on safety and effectiveness are crucial because study by Dalal et al assessing the pharmacokinetic and pharmacodynamic of FDCs concluded that many of the FDCs approved were lacked of rationality [24]. In general, preclinical or clinical safety and efficacy data are not required.…”
Section: Discussionmentioning
confidence: 99%